2022
DOI: 10.1177/09713557211069304
|View full text |Cite
|
Sign up to set email alerts
|

A ‘Dark Side’ of Humane Entrepreneurship? Unveiling the Side Effects of Humane Entrepreneurship on Work–Life Balance

Abstract: Humane entrepreneurship postulates an innovative strategic posture assuming that entrepreneurs should concomitantly focus on the enterprise, the human and the societal cycles of the firm to achieve organisational excellence. Scholars have stressed the economic and societal gains triggered by humane entrepreneurship. However, little is known about its implications for work–life balance (WLB). The article fills in this gap, shedding light into the dark side of humane entrepreneurship on the entrepreneurs’ abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 77 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…In this research, the authors did not test any boundary conditions; future research should test whether high-paying managerial jobs moderate the relationship between narcissism and entrepreneurial intentions. Further, researchers should also explore the relationship between narcissism and intrapreneurship (Yariv & Galit, 2017), and the subjective well-being and work–life balance of employees working under narcissistic intrapreneurs (Palumbo, 2022). Next, this study has explored only one facet of the dark side of personality, that is, narcissism.…”
Section: Discussionmentioning
confidence: 99%
“…In this research, the authors did not test any boundary conditions; future research should test whether high-paying managerial jobs moderate the relationship between narcissism and entrepreneurial intentions. Further, researchers should also explore the relationship between narcissism and intrapreneurship (Yariv & Galit, 2017), and the subjective well-being and work–life balance of employees working under narcissistic intrapreneurs (Palumbo, 2022). Next, this study has explored only one facet of the dark side of personality, that is, narcissism.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to many studying management due to their desire to be promoted or be placed in a managerial role. One way to emphasis real life business contexts in management learning is through work engagement practices ( Palumbo, 2022b ). Work engagement involves “a positive fulfilling work-related state of mind that is characterised by vigour, dedication and absorption” ( Schaufeli, Bakker, & Salanova, 2007 , p. 702).…”
Section: Changes In Management Education Teaching and Learning Methodsmentioning
confidence: 99%
“…A number of previous studies (e.g. Annink et al, 2016;Palumbo, 2022;Parasuraman et al, 1996) have indicated that time demands in some sectors are increasing, further undermining WLBs.…”
Section: Ccsm 312mentioning
confidence: 99%